Epidemiological characterization and risk factors associated with Mycobacterium avium subsp. paratuberculosis infection in dairy goats in the Brazilian semiarid region - Theonys Diógenes Freitas (Semina: Ciências Agrárias, 2015)
The aim of this investigation was to conduct an epidemiological study and identify risk factors associated with the occurrence of paratuberculosis (Johne’s disease) in dairy goats within the semiarid region of Paraíba State. The study was done during the period of March 2009 to July 2011, during which 727 female goats from 86 flocks from the city of Monteiro, Paraíba were investigated. For the serological diagnosis of Mycobacterium avium subsp. paratuberculosis (Map) infection indirect ELISA tests (screening and confirmatory) were performed. Of the 727 animals used six (0.82%) were seropositive at the confirmatory test after screening, and of the 86 flocks six (6.97%) presented at least one seropositive animal. In positive flocks the frequency of reactive animals ranged from 5.26% to 16.60%. Risk factors identified were production system (weaning and reproduction) (odds ratio = 36.0; 95% CI = 2.6 –486.1; p < 0,001) and absence of technical infrastructure (odds ratio = 54.0; 95% CI = 4.5 –642.9; p < 0,001). It was concluded that Mycobacterium avium subsp. paratuberculosis is present in dairy goat flocks in the region; however, its influence on decrease productivity as well as the risk of transmission to humans through animal products must totally evaluated. Based on the analysis of risk factors, improvements are recommended for the technical infrastructure and the management of breeding goats.